The objectives, design and implementation of the INTERGROWTH‐21st Project. (17th May 2013) - Villar, J; Altman, DG; Purwar, M; Noble, JA; Knight, HE; Ruyan, P; Cheikh Ismail, L; Barros, FC; Lambert, A; Papageorghiou, AT; Carvalho, M; Jaffer, YA; et al.
Abstract : Please cite this paper as: Villar J, Altman D, Purwar M, Noble J, Knight H, Ruyan P, Cheikh Ismail L, Barros F, Lambert A, Papageorghiou A, Carvalho M, Jaffer Y, Bertino E, Gravett M, Bhutta Z, Kennedy S, for the International Fetal and Newborn Growth Consortium for the 21 st Century (INTERGROWTH‐21 st ). The objectives, design and implementation of the INTERGROWTH‐21 st Project. BJOG 2013; 120 (Suppl. 2): 9–26. INTERGROWTH‐21 st is a multicentre, multiethnic, population‐based project, being conducted in eight geographical areas (Brazil, China, India, Italy, Kenya, Oman, UK and USA), with technical support from four global specialised units, to study growth, health and nutrition from early pregnancy to infancy. It aims to produce prescriptive growth standards, which conceptually extend the World Health Organization (WHO) Multicentre Growth Reference Study (MGRS) to cover fetal and newborn life. The new international standards will describe: (1) fetal growth assessed by clinical and ultrasound measures; (2) postnatal growth of term and preterm infants up to 2 years of age; and (3) the relationship between birthweight, length and head circumference, gestational age and perinatal outcomes. As the project has selected healthy cohorts with no obvious risk factors for intrauterine growth restriction, these standards will describe how all fetuses and newborns should grow, as opposed to traditional charts that describe how some have grown at a given place and time. These growth patterns will be related to morbidity and mortality to identify levels of perinatal risk. Additional aims include phenotypic characterisation of the preterm and impaired fetal growth syndromes and development of a prediction model, based on multiple ultrasound measurements, to estimate gestational age for use in pregnant women without access to early/frequent antenatal care.